The role of the White paper on defence in the system of defence of the Republic of Serbia - Golubović Marko R. (Војно дело)
On 30th October 2023, the Ministry of Defence of the Republic of Serbia presented the new White Paper on Defence of the Republic of Serbia. Today, after more than a decade from the publication of the previous white paper, a question arises regarding its role in the system of defence. Primarily, this document familiarises the national and foreign public with processes, achievements, and projections for the development of the system of defence of the Republic of Serbia in a transparent and public manner. Changed conditions in which the system of defence of the Republic of Serbia functions that refer to the technological development and modern channels of communication impose a need to review the role of the white paper, which represents the primary problem of the research. In addition to the role of informing national and foreign public, these documents also have a political, and sometimes the role of a guidance. This paper will in greater detail analyse the novelties in the new White Paper on Defence, and compare the role with previous documents, and identify key differences by means of the method of content analysis and comparative analysis. Apart from identifying the roles and novelties in the new White Paper on Defence, the aim of the paper is to provide proposals for the enhancement of the production of new white papers on defence, having in mind their significance in the strengthening of the process of transparency in the field of security and defence. The basic hypothesis of the paper is that the practice of publishing the white paper on defence in the Republic of Serbia exclusively for the purpose of providing information is obsolete, and that it is necessary to redirect the role of future white papers on defence towards a more detailed and concrete definition of the defence policy of the Republic of Serbia.